ACTIVE LEARNING METHODS IN STUDIES: STUDENTS’ OPINIONS AND EXPERIENCES - Šmitiņa, Agita; Margeviča-Grīnberga, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Rapid changes in education and pedagogy are related not only to the global crisis caused by COVID-19, but also to other changes determined by globalization and technological convergence—labour mobility, changes in different professions and changes in teacher–student relations—that are also affected by intergenerational differences. Changes in the pedagogical paradigm, which are included in the content of the Paris Communiqué (2018) and outlined in many important educational development and planning documents, emphasise students’ transition from being mere recipients of information to being participants actively engaged with new information in a learning environment. Following the identification of problems with a less frequent use of active participation methods in higher education, the University of Latvia implemented an Erasmus+ project entitled Entrance to Future Education (2017–2019). In this project, the authors summarized modern, inspiring, interactive, active engagement-oriented teaching/learning methods in higher education. During the project, several student focus groups were formed to discuss students’ experiences with active engagement methods in studies, and a handbook with various student active engagement methods and games was created. In 2020, 106 students from different Latvian universities were surveyed about their understanding and experience in relation to these teaching methods in their studies. The results showed that, according to students, attitude and ardour are essential for engaging students with enthusiasm and interest in the study process. The results of the survey show the varied experiences of students, as well as different understandings of active learning methods. Students noted that they most often experienced various group projects in studies, presentations and various tasks outside the classroom, but relatively rarely used such methods as creative video making, active use of game elements and constructive feedback from peers